Development and performance determination of warm mix asphalt using rap for Malaysian conditions / Frag Ahmed Ma Kridan - Ma Kridan, Frag Ahmed (Institute of Graduate Studies, UiTM, 2014)
Current concerns on the scarcity of resources necessitate the road building industry to review its production of asphaltic concrete. The use of Warm Mix Asphalt (WMA) technologies with asphalt mixtures containing reclaimed asphalt pavement (RAP) may provide synergistic advantages. WMA-RAP mixes conserves scarce resources such as aggregates by using RAP as partial replacement of aggregates and reduces the use of energy (reduction in production temperature) by using WMA additives. Most specifications allow not more than 30% RAP as higher percentages of RAP introduces variability in the material properties and produces inconsistencies in asphalt mix properties. The goal of this study was to evaluate the performance of warm mix asphalt with high proportions of RAP (30%, 40% and 50%) and using Sasobit as the warm mix additive to reduce the mixing and compaction temperature.